2021
DOI: 10.1007/s11095-021-03059-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prototype, Once-Daily, Modified-Release Formulation for the Short Half-Life RIPK1 Inhibitor GSK2982772

Abstract: Purpose GSK2982772 is a selective inhibitor of receptor-interacting protein kinase-1, with a 2–3 h half-life. This study evaluated if a once-daily modified-release formulation of GSK2982772 could be developed with no significant food effect. Methods Part A evaluated the pharmacokinetics of GSK2982772 following fasted single-dose (120 mg) administration of two matrix minitab formulations (MT-8 h and MT-12 h) vs 120 mg immediate release (IR) and MT-12 h with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Taken together, these results do not support the notion that RIPK1 inhibition alone at the level achieved in this study could translate into transformative improvement of UC. [27][28][29] Other limitations to the study include the relatively small sample size and that baseline information regarding disease severity, including Montreal classification, was not collected. The impact of disease heterogeneity between treatment groups may have affected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results do not support the notion that RIPK1 inhibition alone at the level achieved in this study could translate into transformative improvement of UC. [27][28][29] Other limitations to the study include the relatively small sample size and that baseline information regarding disease severity, including Montreal classification, was not collected. The impact of disease heterogeneity between treatment groups may have affected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the previous prototype matrix formulation study were used to help pre-define the range of in vitro release rates of GSK2982772 to test in the current study. It was anticipated that in the fasted state, the DiffCORE technology tablet should exhibit similar behavior in vivo to the previously tested MM tablets, since both formulations had a similar core matrix formulation ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For chronic inflammatory conditions, a once-daily (QD) dosing option would offer greater convenience, potentially improve compliance and therapeutic outcome, and offer a flatter concentration–time profile with lower peak-to-trough concentrations compared with the IR formulation. A previous study evaluated matrix-based MR formulations of GSK2982772 administered as either minitablets (MT) or matrix monolithic (MM) tablets using two in vitro dissolution rates: a) 80% GSK2982772 released over 8 h, and b) 80% GSK2982772 released over 12 h ( 13 ). This previous study showed that a QD pharmacokinetic (PK) profile could be achieved in the fasted state with the slower in vitro dissolution rate of 80% release over 12 h (MT-12 h and MM 12 h).…”
Section: Introductionmentioning
confidence: 99%
“…Lesional biopsies taken on day 43 showed improvements in epidermal thickness and lymphocyte infiltration (CD3 + T cell) relative to baseline and placebo [ 70 ]. A modified release-formulation of the drug is currently under development to compensate for the drug’s short half-life and allow for a once-daily dosing option for patients [ 71 , 72 ]. This new formulation proved successful in preclinical trials and was recently investigated in a phase I trial (NCT04316585) for psoriasis [ 71 ].…”
Section: Pipeline Therapiesmentioning
confidence: 99%